Effect of chronic somatic diseases on the course of late‐life depression. (7th June 2016) - Hegeman, Johanna M.; van Fenema, Esther M.; Comijs, Hannie C.; Kok, Rob M.; van der Mast, Roos C.; de Waal, Margot W.M.
Abstract : Objective: To examine the influence of specific chronic somatic diseases and overall somatic diseases burden on the course of depression in older persons. Methods: This was a prospective cohort study with a 2‐year follow‐up. Participants were depressed persons ( n = 285) from the Netherlands Study of Depression in Older Persons. The presence of chronic somatic diseases was based on self‐report. Diagnosis of depression was assessed with the Composite International Diagnostic Interview, and severity of depression was measured with the Inventory of Depressive Symptomatology Self‐report. Results: Cardiovascular diseases (odds ratio [OR] = 1.67, 95% confidence interval [CI] = 1.02–2.72, p = 0.041), musculoskeletal diseases (OR = 1.71, 95% CI = 1.04–2.80, p = 0.034), and the number of chronic somatic diseases (OR = 1.37, 95% CI = 1.16–1.63, p < 0.001) were associated with having a depressive disorder at 2‐year follow‐up. Furthermore, chronic non‐specific lung diseases, cardiovascular diseases, musculoskeletal diseases, cancer, or cumulative somatic disease burden were associated with a chronic course of depression. Conclusions: Somatic disease burden is associated with a poor course of late‐life depression. The course of late‐life depression is particularly unfavorable in the presence of chronic non‐specific lung diseases, cardiovascular diseases, musculoskeletal diseases, and cancer. Copyright © 2016 John Wiley & Sons, Ltd.